APLIKASI PUPUK ORGANIK CAIR (POC) PADA MEDIUM VACIN AND WENT (VW) TERHADAP PERTUMBUHAN PLANLET ANGGREK Dendrobium sp. SECARA IN VITRO - Purnama Agustin, Kharisma; Nurcahyani, Endang; Wahyuningsih, Sri; Irawan, Bambang (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2026)
Dendrobium is a popular ornamental plant in Indonesia, but its production is often hindered by the lack of superior seedlings and low cultivation efficiency. Fertilization containing macro- and micronutrients, along with growth hormones, can enhance orchid growth. Liquid organic fertilizer (LOF) is considered more efficient than solid fertilizers because it is easily absorbed by roots, accelerates photosynthesis, and promotes new tissue formation. One easily accessible LOF is Amino Age. This study aimed to determine the effect and optimal concentration of Amino Age LOF on the in vitro growth of Dendrobium sp., plantlets. The study employed a Completely Randomized Design (CRD) with a single factor, namely LOF concentration (0 ml/L as control, 1 ml/L, 1.5 ml/L, 2 ml/L, and 2.5 ml/L) and five replications. The data were analyzed using ANOVA and followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that Amino Age LOF had a significant effect on the growth of Dendrobium sp. plantlets. The optimal concentration was 2 ml/L, which yielded the best results in terms of plantlet survival rate, growth visualization, stomatal density, fresh weight, and dry weight. Keywords: Dendrobium sp., Amino Age Liquid Organic Fertilizer (LOF), In Vitro Culture, Completely Randomized Design (CRD).